The Analysis of the Impact of Mobile Number Portability in Nigeria - N, Odii Juliet; E., Ejiofor V irginia; ma. L, Okpalla Chidim (International Journal For Research In Advanced Computer Science And Engineering, 2016)
Mobile Number Portability (MNP) launched in Nigeria in 2013 was meant to improve quality of service and other service concerns by deepening competition among telecom service providers but has unfortunately failed to do so. Three years after its implementation there is still a growing disillusionment on MNP by Nigerians. The objective of this research therefore is to empirically analyze the impact of MNP in Nigeria telecommunication since its inception. The methodologies that were deployed include hypothetic deductive methodology using questionnaire to collect the field data and the statistical analysis methodology using multiple regressions and ANOVA to extract the P-value. The result obtained shows a P- value of 3.3E160 which is greater than zero and F-cal α0.05 =147.376 is greater than Fcritical α0.05 =2.102, indicating that the null hypothesis should be accepted while the alternative hypothesis should be rejected. This research has therefore empirically shown that MNP has actually failed to produce the desired impact contrary to the expectation of the Nigerian Communication Commission.